Pengaturan Sarana Dan Metode Perang Dalam Perspektif Hukum Humaniter Internasional: Studi Atas Konvensi Den Haag 1907 Dan Protokol Tambahan 1977 - Aldo Syahputra; Lusi Apriyani; Tri Sulistyaningsih; Annisa Alif Nur Nariyah (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
War, as a historical and contemporary phenomenon, brings not only military impacts but also widespread humanitarian suffering. In this context, international humanitarian law exists to limit the methods and means of warfare while providing protection for war victims. This study examines the regulation of methods and means of warfare based on the 1907 Hague Convention and its 1977 Additional Protocol, focusing on basic principles such as distinction, proportionality, and military necessity. Furthermore, this study examines the protections afforded to civilians, combatants no longer capable of fighting, and civilian objects vital ti the survival of society. Through a normative review on international lega; intrumens, this sstufy confirms that the principle of distinction between military and civilian targets ia a central pillar of humanitarian law. The 1907 Hague Convention limits the methods of warfare, while the 1977 Additional Protocol expands protection for war victims, including prohibiting the use of starvation as a method of warfare and obligating civil defense. The research findings demonstrate that humanitarian law strives to maintain a balance between military and humanitarian interest. Therefore, this study emphasizes the importance of compliance bt states and conflicting parties with humanitarian law intruments so that the primary objective limiting human suffering in war can be effectively realized.